PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VII 3 DALAM PEMBELAJARAN SENI RUPA MELALUI PENGGUNAAN MODEL EXAMPLES NON EXAMPLES DI SMP NEGERI 12 PADANG - SITI AISYAH, Yusron Wikarya, Zubaidah (Serupa The Journal of Art Education, 2013)
The purpose of this research are to (1) know increase student’s motivation in study fine art using Examples Non Examples model (2) know increase result study of student in study fine art using Examples Non Examples. Study model which in purpose is Examples Non Examples model. Source of this research is student class VII 3 SMP Land 12 Padang, with using observation, registered wide, questionnaire and result study tes. The result are (1) there is increasing of student’s motivation from siklus I is 3, 25 to siklus II is 4, 01. (2) there is increasing result study of student from pra siklus is 64, 24 to siklus I is 72, 24 and siklus II 84, 14.